2020
DOI: 10.7759/cureus.6662
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nocturnal Enuresis among Saudi Children Population

Abstract: Background Nocturnal enuresis (NE) is the involuntary urination that occurs while asleep after an age when bladder control at night is expected. It has a global incidence of 1.4%-28% among 6-12 years old children. The aim of this study is to show the prevalence, risk factors, types of provided treatment of enuresis among studied children in Kingdom of Saudi Arabia (KSA). Methods A cross-sectional descriptive study was carried out among Saudi children, 3-12 years of age, from different cities in Saudi Arabia, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
32
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 18 publications
6
32
2
1
Order By: Relevance
“…Our study supported this, as the prevalence peaked at 65% in children between six and seven years of age and decreased in older age groups. This finding is similar to prior studies, which also reported the highest prevalence among six to seven-year-old participants [15,22].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study supported this, as the prevalence peaked at 65% in children between six and seven years of age and decreased in older age groups. This finding is similar to prior studies, which also reported the highest prevalence among six to seven-year-old participants [15,22].…”
Section: Discussionsupporting
confidence: 92%
“…According to our results, 60% of enuretic children had daytime and nighttime symptoms, which is congruent with a Saudi study where 55% of children had such symptoms [15]. However, one study reported a lower prevalence of 18% of daytime symptoms [25].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Several studies have shown that the NE level decreases as age increases [12]. According to Alhifthy et al [13] the prevalence of NE was 63% at the age of 6-7 years and 4.5% at the age of 10-12 years old that is consistent with previous reports [5,14]. In this study, the order of birth was not significantly different between both groups, and this agrees with a Turkish study that reported no association between birth order and the prevalence of NE [15].…”
Section: Discussionmentioning
confidence: 99%